A systematic review of interventions to provide genetics education for primary care. Issue 1 (December 2016) - Paneque, Milena; Turchetti, Daniela; Jackson, Leigh; Lunt, Peter; Houwink, Elisa; Skirton, Heather
Abstract Background At least 10 % of patients seen in primary care are said to have a condition in which genetics has an influence. However, patients at risk of genetic disease may not be recognised, while those who seek advice may not be referred or managed appropriately. Primary care practitioners lack knowledge of genetics and genetic testing relevant for daily practice and feel inadequate to deliver genetic services. The aim of this systematic review was to evaluate genetics educational interventions in the context of primary care. Methods Following the process for systematic reviews developed by the Centre for Reviews and Dissemination, we conducted a search of five relevant electronic databases. Primary research papers were eligible for inclusion if they included data on outcomes of interventions regarding genetics education for primary care practitioners. The results from each paper were coded and grouped under themes. Results Eleven studies were included in the review. The five major themes identified inductively (post hoc) were: prior experience, changes in confidence, changes in knowledge, changes in practice, satisfaction and feedback. In five of the studies, knowledge of practitioners was improved following the educational programmes, but this tended to be in specific topic areas, while practitioner confidence improved in six studies. However, there was little apparent change to practice. Conclusions There are insufficient studies of relevant quality to inform educational interventions in genetics for primary care practitioners. Educational initiatives should be assessed using changes in practice, as well as in confidence and knowledge, to determine if they are effective in causing significant changes in practice in genetic risk assessment and appropriate management of patients.